Faecal fat excretion after truncal, selective, and highly selective vagotomy for duodenal ulcer - Edwards, J. P. (1974)
Faecal fat excretion was measured on a metabolic ward in 16 patients with duodenal ulcer before operation, and in patients who were in good health more than one year after truncal vagotomy and pyloroplasty (n = 11), bilateral selective vagotomy and pyloroplasty (n = 9), or highly selective vagotomy without a drainage procedure (HSV, n = 12). Excretion of faecal fat was significantly greater (p < 0·01) in patients after both truncal and selective vagotomy with drainage than in patients before operation. Fat excretion in HSV patients was little different from that of preoperative patients. If steatorrhoea is defined as a faecal fat output of more than 6 g per day, one of 16 preoperative patients with duodenal ulcer (6%) had steatorrhoea, one of 12 HSV patients (8%) had steatorrhoea, one of nine patients after selective vagotomy and pyloroplasty (11%) had steatorrhoea but five of 11 patients after truncal vagotomy and pyloroplasty (45%) had steatorrhoea.